ANALISIS KEBUTUHAN MULTIMEDIA INTERAKTIF BERBASIS GAME PADA MATERI PERKALIAN DI SEKOLAH DASAR - Marwiyyah, Linda; Karlimah; Asep Nuryadin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background to this research is based on conditions in the field, namely that there are still many students who experience difficulties in understanding the basic concepts of multiplication calculation operations, as well as the limited use of innovative learning media in the classroom. This research aims and is useful to analyze the need for developing game-based interactive multimedia on multiplication material in elementary schools, so that it can provide alternative learning media that are more interesting, easy to access, and in accordance with student characteristics. The research method used was a qualitative approach with data collection techniques through interviews with class III teachers at SDN Condong, Tasikmalaya City. The results and discussion show that teachers in learning activities use the Contextual Teaching Learning (CTL) approach, with the lecture method, and media in the form of concrete objects around them and learning videos. However, teachers have not utilized game-based interactive multimedia, even though this media is considered to have great potential to increase student motivation and understanding. Teachers also hope that there will be learning media that is interactive, fun, easy to access, and in accordance with the cognitive needs of class III students. Thus, it can be concluded that there is a need for the development of game-based interactive multimedia that can facilitate visual and kinesthetic learning styles, as well as support the achievement of competencies in the Independent Curriculum.